2021
DOI: 10.1002/adfm.202109741
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Magnetic FePt (L10) Surface Microrollers Towards Medical Imaging‐Guided Endovascular Delivery Applications

Abstract: Controlled microrobotic navigation in the vascular system can revolutionize minimally invasive medical applications, such as targeted drug and gene delivery. Magnetically controlled surface microrollers have emerged as a promising microrobotic platform for controlled navigation in the circulatory system. Locomotion of micrororollers in strong flow velocities is a highly challenging task, which requires magnetic materials having strong magnetic actuation properties while being biocompatible. The L10‐FePt magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 52 publications
2
58
0
Order By: Relevance
“…Another study showed the visualization of 100-μm-long helical microrobots inside phantoms and ex vivo chicken breasts ( 40 ). OAT was used to visualize FePt-coated spherical microrobots that were directly injected into the muscular tissue of a dead mouse ( 41 ). The visualized particle agglomeration consisted of around 30,000 individual microrobots while the image acquisition took 45 min due to the low optical absorption contrast exhibited by the robots that were not optimized for sensitive OAT detection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed the visualization of 100-μm-long helical microrobots inside phantoms and ex vivo chicken breasts ( 40 ). OAT was used to visualize FePt-coated spherical microrobots that were directly injected into the muscular tissue of a dead mouse ( 41 ). The visualized particle agglomeration consisted of around 30,000 individual microrobots while the image acquisition took 45 min due to the low optical absorption contrast exhibited by the robots that were not optimized for sensitive OAT detection.…”
Section: Introductionmentioning
confidence: 99%
“…Even in the case of soft-bodied deformable microrobots, their size should not exceed 10 to 20 μm to allow for safe travel through capillaries ( 22 ). Moreover, the insufficient optical absorption contrast of microrobot materials used in previous studies has restricted the monitoring ability to large-sized robots or otherwise large particle agglomerates under ex vivo conditions ( 41 ). Last, no simultaneous actuation and tracking under OAT have so far been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…It becomes more challenging to achieve light-driven out-ofplane rotation (i.e., rotation of an object around an axis parallel to the substrate) (24,25). By enabling three-dimensional (3D) interrogation of objects such as biological particles, out-of-plane rotation techniques would improve rolling cell adhesion measurements (26,27), single-cell engineering (28), organism identification (29), and microsurgery (30)(31)(32)(33). Recently, light-driven out-of-plane rotation has only been realized using multiple-beam optical tweezers (10,34) or combining light with a microfluidic field (35) or an external electric field (36).…”
Section: Introductionmentioning
confidence: 99%
“…[33] Bozuyuk et al demonstrated upstream navigation of magnetic micro rollers on various 3D surface micro topographies. [34,35] Finally, Wang et al used magnetic swarms that could assemble in stagnant Navigation of microrobots in living vasculatures is essential in realizing targeted drug delivery and advancing non-invasive surgeries. Acousticallycontrolled "swarmbots" are developed based on the self-assembly of clinically-approved microbubbles (MBs).…”
mentioning
confidence: 99%